The Effect of Product Quality, Brand Equity and Word of Mouth (WOM) on Customer Loyalty Jamu Tolak Angin at Indomaret Pasar Pekan South Jakarta - Khoir, Ahmad; Hardini, Resti; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to analyze the Effect of Product Quality, Brand Equity and Word of Mouth (WOM) on Jamu Tolak Angin Customer Loyalty at Indomaret Pasar Minggu, South Jakarta. In this study using primary data obtained from the distribution of questionnaires. The sample in this study was 96 respondents using probability sampling techniques. This study used Multiple Linear Regression analysis using SPSS program version 23.0. The results of this study show that product quality has a positive and significant influence on customer loyalty. This can be seen from the results of the t test where t is calculated (2.367) > t table 1.6608 and the signification value is 0.020 so that (0.020 < ? 0.05). Brand equity has a positive and significant influence on customer loyalty. This can be seen from the results of the t test where t is calculated (4.958) > t table 1.6608 and the signification value is 0.000 so that (0.000 < ? 0.05). Word of Mouth (WOM) has a positive and significant influence on customer loyalty. This can be seen from the results of the t test where t is calculated (3.521) > t table 1.6608 and the signification value is 0.001 so that (0.001 < ? 0.05)